Sistema de educación financiera y su incidencia en los emprendimientos en la ciudad de Quevedo, año 2023 - Cedeño Aguirre , Yanina Lisseth (2024)
The purpose of the research was to determine the impact of the financial education system on the development of entrepreneurship in the city of Quevedo. The methodology followed a descriptive approach to analyze the influence of the financial education system on entrepreneurship. Primary and secondary data were collected through surveys and interviews with local entrepreneurs and representatives of the Chamber of Commerce. The interviews with the director of the Chamber of Commerce made it possible to diagnose the classification of the ventures and success factors. A research instrument was designed based on Likert and open questions, validated according to established protocols. In addition, strategies were proposed to promote financial education, considering the results obtained. The initial population of 300 entrepreneurs was reduced to 123, representing a response rate of 41%. The results highlight entrepreneurial diversity, reflecting its economic vitality, although it faces challenges. The resilience of local entrepreneurs highlights the importance of informal commerce in the economy. However, low financial education highlights the need for training to improve business management and sustainability. The research reveals a significant relationship between financial education and business performance, although there is diversity in the perception of those surveyed. The importance of implementing financial education training strategies to boost business viability is highlighted, despite diverse opinions on the accessibility and effectiveness of educational programs. In conclusion, it is essential to strengthen financial education as a fundamental strategy for the success and sustainability of ventures in Quevedo.